Case report: Localized coloproctitis caused by novel Basidiobolus arizonensis in a dog - Black, Annalise; Wiertek, Marcellina; Ferguson, Sylvia; Wycislo, Kathryn; Rayhel, Laura; Reid, Heather; Wiederhold, Nathan; Cañete-Gibas, Connie (Frontiers in Veterinary Science, 2024)
A 6-year-old male neutered boxer mix canine was presented for a one-month history of dyschezia, hematochezia, and constipation. Colonoscopy and endoscopic biopsies revealed non-specific lymphoplasmacytic, eosinophilic colitis. Despite pursuing various therapies over a 3.5-month clinical course (including hypoallergenic diet, antibiotics, prokinetics, laxatives, and anti-inflammatory glucocorticoids), the patient’s condition did not improve. Two and a half months after initial presentation, the patient developed circumferential proctitis with multiple draining tracts and obstipation. Humane euthanasia and postmortem examination were elected. Gross and histological findings revealed locally extensive pyogranulomatous coloproctitis with many intralesional PAS-positive, GMS-negative 30–40 μm in diameter, hyaline, pauciseptate, irregularly branching fungal hyphae, hyphal bodies or chlamydospores and 25–45 μm in diameter thick-walled zygospores. Fungal culture of fluid from the draining tracts was performed, and DNA sequence analysis of the ITS and partial LSU of the nuclear ribosomal RNA genes were used to identify and confirm a novel species, Basidiobolus arizonensis. Basidiobolus spp. are saprobes in the order Basidiobolales and most commonly cause granulomatous infections of the skin, respiratory tract, and gastrointestinal tract in veterinary species and humans. To the authors’ knowledge, this is the first report of novel Basidiobolus arizonensis causing localized coloproctitis in a dog.